Human Rights Protection and Terrorism - Reflections in the Context of Strasburg Jurisprudence - Kowalska, Samanta (Matej Bel University, Faculty of Political Sciences and International Relations /// Univerzita Mateja Bela v Banskej Bystrici, Fakulta politických vied a medzinárodných vzťahov, 2015)
The phenomenon of terrorism is one of the most asymmetrical, amorphous and hybrid threats to international security. At the beginning of the 21st century, terrorism grew to a pandemic. Ensuring freedom and security of individuals and nations has become one of the priority postulates. Terrorism steps out of all legal and analytic-descriptive standards. An immanent feature of terrorism, e.g. is constant conversion into malicious forms of violence. One of the most alarming changes is a tendency for debasement of essence of law, a state and human rights. Assurance of safety in widely accessible public places and in private life forces creation of various institutions, methods and forms of people control. However, one cannot in an arbitrary way limit civil freedom. Presented article stresses the fact that rational and informed approach to human rights should serve as a reference point for legislative and executive bodies. Selected individual applications to the European Court of Human Rights are presented, focusing on those based on which standards regarding protection of human rights in the face of pathological social phenomena, terrorism in particular, could be reconstructed and refined. Strasbourg standards may prove helpful in selecting and constructing new legal and legislative solutions, unifying and correlating prophylactic and preventive actions.
Keywords: terrorism; terror; human rights; international law; european law; case-law and judgements of the European Court of Human Rights; international relations; anti-terrorism legislation